Conversational AI for Santripreneurs: Enhancing Business Communication Skills in an Informal-Religious Educational Context - Maisarah, Maisarah; Al-Dhahli, Faiza; Setyobudi, Bambang; Masrur, Mukhamad (FKIP Universitas Lampung, 2025)
Conversational AI for Santripreneurs: Enhancing Business Communication Skills in an Informal-Religious Educational Context. Objectives: This paper evaluates the effectiveness of a chatbot-assisted training program in enhancing business communication among young entrepreneurs in Islamic boarding schools (pesantren), referred to as